Knowledge, Attitudes and Practices of Farmers on Rodent Pests and their Management in Cold Arid Ecosystem of Leh, Jammu & Kashmir, India - Chaudhary, Vipin; Meena, R.C.; Singh, Surjeet; Tripathi, R.S. (Annals of Arid Zone, 2023)
Rodent pests are one of the major biotic constraints in agricultural production.Agriculture being the main occupation of rural population of the cold arid district ofLeh, crop production suffers greatly due to rodent depredation in fields and storage.A structured survey of 200 farmers from 10 villages across the district was carried outduring July-September, 2018 to assess the farmers’ knowledge, attitudes and practiceswith respect to rodent management. The study revealed that pests in general are amajor limitation (43% respondents), followed by poor soil (31.5%), insufficient labor(15%), insufficient irrigation water (4%), flooding (1.5%) and high cost of cultivation(1%). The farmers identified rodents as the major pest (46.5%) on their farms, followedby insects (35.5%), disease (14%), none (2.5%) and others (1.5%). The overall estimatedyield loss due to rodents was 18.33%. Most of the farmers (77.7%) thought that cropyields could be increased by controlling rodents and opined that they could controlrodents if they worked together through community action, although 63% were doingrodent control individually. A Majority of farmers were of opinion that chemical control(i.e., use of rodenticides in baits) was the best option but they were not aware aboutthe risk posed by such chemicals to non-target species (53%). The farmers’ could benefitfrom training and education on various aspects of rodent technologies including usinga community approach.